Nitzschia taikiensis sp. nov. (Bacillariophyta) – a new brackish diatom from the Toberi River marsh in the eastern Hokkaido, Japan - Chiba, Takashi; Nishimura, Yuichi; Horie, Yoshifumi; Tuji, Akihiro (Biodiversity: Research and Conservation, 2020)
Nitzschia taikiensis sp. nov. is a brackish diatom species found in the Toberi River marsh, eastern Hokkaido, Japan. This species has characteristics similar to Nitzschia subamphioxoides Hustedt, which was originally described by Hustedt in 1959. In the present study, we conducted a comparative morphological analysis of N. taikiensis and N. subamphioxoides. The obtained results showed that they are different species. Sampling sites of N. taikiensis were located in salt marsh environments with very low salinity (1-5‰), acidic pH (5.2-5.9) and high mud content (95.0-97.5%). Identification of this species was relatively easy based on LM and SEM image analysis of its frustule features, such as the external form and stria density. This species has not been previously reported in Japan, which could be attributed to the reduction or loss of Japanese freshwater and salt marsh environments in the coastal areas, resulting from urban and industrial development.